Optimizing the Role of Mediators in Realizing Peace Deeds: A Study of Mediation at the Religious Court of Padangsidimpuan City - Rohana, Nada Putri (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The role of the mediator is crucial in resolving problems in the mediation stage. The peace deed obtained from successful mediation has the same legal force as a court decision, meaning that the deed can be carried out and executed like a judge's decision. The Padangsidimpuan City Religious Court has judges and non-judge mediators who have different backgrounds, including judges, lawyers, and lecturers. So that with this diversity of backgrounds, each of the mediators carries out their role in solving problems. This study aims to determine how to optimize the role of the mediator in the mediation process to obtain a peace deed and find out about it. The research was conducted using a field research method to determine legal justice in the priority of knowing the role of the mediator and obtaining a peace deed. Data collection was carried out by means of observation, interviews, and documentation of data relevant to the study in study. From the results of the study, it can be concluded that the role of the mediator in resolving mediation cases is determined based on the acquisition of a peace deed. The acquisition of peace deeds obtained from data from 2021-2023 obtained 3 peace deeds from a total of 74 mediation cases. [Peran mediator menjadi krusial dalam menyelesaikan masalah dalam tahapan mediasi. Akta perdamaian yang diperoleh dari keberhasilan mediasi memiliki kekuatan hukum yang sama dengan putusan pengadilan, artinya akta dapat dijalankan dan dieksekusi seperti putusan hakim. Pengadilan Agama Kota Padangsidimpuan memiliki mediator hakim dan non hakim yang memiliki latar belakang berbeda diantaranya hakim, pengacara, dan dosen. Sehingga dengan keberagaman latar belakang ini menjadikan masing-masing dari mediator melaksanakan perannya dalam penyelesaian masalah. Penelitian ini bertujuan untuk mengetahui bagaimana mengoptimalkan peran mediator dalam proses mediasi untuk memperoleh akta perdamaian dan mengetahuinya. Penelitian dilakukan dengan metode penelitian lapangan untuk mengetahui keadilan hukum dalam prioritas mengetahui peran mediator dan memperoleh akta perdamaian. Pengumpulan data dilakukan dengan cara observasi, wawancara dan dokumentasi data-data yang relevan dengan kajian dalam penelitian ini. Dari hasil penelitian dapat disimpulkan bahwa peran mediator dalam menyelesaikan perkara mediasi ditentukan berdasarkan diperolehnya akta perdamaian. Perolehan akta perdamaian yang didapatkan dari data tahun 2021-2023 diperoleh 3 akta perdamaian dari jumlah perkara mediasi 74 perkara].